2013
DOI: 10.1371/journal.pone.0077947
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Psychometric Properties of the Functional Assessment of Cancer Therapy-Cervix Questionnaire in Brazil

Abstract: BackgroundAlthough cervical cancer is ​​the second most common tumor among Brazilian women, studies that evaluate the quality of life of these women are still scarce. This situation is explained by the lack of specific and validated tools for this purpose in Portuguese (Brazil). The aim of this study was to evaluate the psychometric properties of the Portuguese version of the FACT-CX (Functional Assessment of Cancer Therapy-Cervix) questionnaire in a population of Brazilian women with cervical cancer.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
0
16
2
15
Order By: Relevance
“…Nowadays, there are 2 common specific measurements for quality of life in cervical cancer: Functional Assessment of Cancer Therapy with Cervical Cancer Subscale (FACT-CX) and the Cervical Cancer Module (QLQ-CX24) from the European Organization for Research and Treatment of Cancer Quality of Life. FACT-CX is a cervical cancer specific quality of life questionnaire that has been be validated in English, Chinese and Portuguese (Ding et al 2012;Fregnani et al 2013). FACT-CX uses 42 items.…”
Section: Validation Of the Functional Assessment Of Cancer Therapy Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, there are 2 common specific measurements for quality of life in cervical cancer: Functional Assessment of Cancer Therapy with Cervical Cancer Subscale (FACT-CX) and the Cervical Cancer Module (QLQ-CX24) from the European Organization for Research and Treatment of Cancer Quality of Life. FACT-CX is a cervical cancer specific quality of life questionnaire that has been be validated in English, Chinese and Portuguese (Ding et al 2012;Fregnani et al 2013). FACT-CX uses 42 items.…”
Section: Validation Of the Functional Assessment Of Cancer Therapy Wimentioning
confidence: 99%
“…However, the variance included only the variables of the PWB, SWB, FWB and EWB. Another study, by Fregnani et al, (2013) not report the Kaiser-Meyer-Olkin sampling adequacy or Bartlett's test of sphericity. The suitability of samples for performing EFA is unknown.…”
Section: Study Included 400mentioning
confidence: 99%
“…This result may have occurred because the SF-12 is a generic questionnaire that does not specifically address the questions explored in the FACIT-CD; therefore, the purposes of the evaluations were distinct. Another study that used a generic and a specific questionnaire reported the same problem when correlating the questionnaires [ 33 ]. This analysis was also conducted using the EORTC QLQ-CX24 questionnaire, which was developed to assess the HRQoL of women with cervical cancer and could easily calculate the scores of the scales and some items separately.…”
Section: Discussionmentioning
confidence: 99%
“…Baseados nos achados da etapa 1, a revisão sistemática de Tax et al 27 questionário utilizado em todo o mundo para avaliação da qualidade de vida de mulheres com câncer do colo do útero e apresenta boas propriedades psicométricas na população brasileira, possuindo capacidade discriminatória para diferenciar mulheres de acordo com a sua percepção de saúde 29 . O EORTC QLQ-CX24 é composto por 24 questões que avaliam a qualidade de vida de mulheres em tratamento para o câncer do colo do útero a partir da funcionalidade e de alguns sintomas específicos 30 .…”
Section: Métodounclassified